1999
DOI: 10.1080/15257779908043078
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Recombinant Herpes Simplex Virus Type 1 Thymidine Kinase with Thymidine and Aciclovir: A Kinetic Study

Abstract: Herpes Simplex Virus type 1 thymidine kinase (HSV 1 TK) is a key target for antiviral therapy and it phosphorylates a broad spectrum of nucleosides and nucleotides. We report the results from kinetic and inhibition experiments with HSV 1 TK, and show that there is a preferred, but not exclusive, binding order of substrates, i.e. dT binds prior to ATP. Furthermore, the results provide new informations on the mechanism of binding suggesting that HSV1 TK undergoes conformational changes during the catalytic cycle. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Moreover, the radiometric results show a K m value of n-MCT corresponding to the K i value of 11.4 Ϯ 1.6 M published by Prota et al (17). This confirms that the K i is equal to the K m in the case of HSV-1 TK, as reported earlier (17,19,20).…”
Section: N-mct Radiometric Assaysupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the radiometric results show a K m value of n-MCT corresponding to the K i value of 11.4 Ϯ 1.6 M published by Prota et al (17). This confirms that the K i is equal to the K m in the case of HSV-1 TK, as reported earlier (17,19,20).…”
Section: N-mct Radiometric Assaysupporting
confidence: 91%
“…New (7); c radiometric study (19); d radiometric study (21); e radiometric study (20); f binding affinities reported as K i in Griffiths (27). In the case of HSV-1 TK, K m and K i values can both be used as binding affinity constant because K m is equal to K i (20).…”
Section: Easy Determination Of the K Cat Values Of Antiviral Lead Commentioning
confidence: 97%
See 1 more Smart Citation
“…Table I shows that the measured k cat of dT agrees with those reported in literature (31,32). Also the k cat of ACV corresponds to that measured in two independent laboratories (33,34). In the literature a value of 0.015 s Ϫ1 is also reported for ACV (31), but, considering the newly reported values, this seems to be an outliner.…”
Section: Catalytic Activity Of Tk Hsv1supporting
confidence: 76%
“…In our attempt to rationalize this property, we have designed a series of (47)(48)(49). This represents a peculiarity of HSV 1 TK by which dT is binding prior to ATP, and the rate constant of disintegration of the intermediate complex (ES) is negligible as compared to the corresponding dissociation rate constant (46).…”
Section: Discussionmentioning
confidence: 99%